Validation of Spanish Language Evaluation Instruments for Body Dysmorphic Disorder and the Dysmorphic Concern Construct - Senín-Calderón, Cristina; Valdés-Díaz, María; Benítez-Hernández, Ma M.; Núñez-Gaitán, Ma C.; Perona-Garcelán, Salvador; Martínez-Cervantes, Rafael; Rodríguez-Testal, Juan F. (Frontiers in Psychology, 2017)
Dysmorphic concern refers to excessive preoccupation with a slight or imagined defect in physical appearance with social avoidance and behavior directed at controlling the defect in appearance. This study attempted to adapt the factor structure of two instruments that cover the dysmorphic concern construct, the Dysmorphic Concern Questionnaire (DCQ) and the Body Dysmorphic Disorder Examination Self-Report (BDDE-SR), to Spanish and establish their psychometric properties. 920 subjects (62.7% women, Mage=32.44 yrs) participated. Exploratory and confirmatory factor analysis of both scales found adequate goodness of fit indices. A one-dimensional structure was found for the DCQ and two first-order factors (Dissatisfaction /preoccupation with body image and body-image avoidance behavior) were identified for the BDDE-SR within a higher-order factor (dysmorphic concern). The psychometric test-retest reliability and validity properties (content, convergent, discriminant and predictive) were satisfactory. It is suggested that the dysmorphic concern construct includes both cognitive and behavioral aspects and may represent a continuum of severity with Body Dysmorphic Disorder at the end.